A review of technology commercialization research: Current research trend and directions for future research - Fithri, Prima; Hasan, Alizar; Syafrizal, Syafrizal; Games, Donard (RSF Conference Series: Business, Management and Social Sciences, 2022)
This study explores academic research on technology commercialization. Technology commercialization is currently a popular research topic. Universities urgently need the topic of commercialization of technology to capitalize on research products. Many universities are having difficulties with this issue, but this is also a moment for them to benefit from innovation and commercialization. The present study offers opportunities, especially regarding the critical success factors affecting technology commercialization. Therefore, the present study discusses both existing and future research related to technology commercialization. By using publish or perish (PoP) 8, the Authors collected 200 papers related to studying future research opportunities. From 200 papers, 127 papers 127 journals for further study. Among them are 53 papers from Q1 (Scopus indexed), 27 papers from Q2, nine papers found from Q3, and five papers from Q4. It was found that current research trends on this topic predominantly come from developed countries such as the USA, UK, and Italy. Many of them used a qualitative approach that focused on prominent and state universities. Future research may focus on the context of emerging market economies. In addition, combining both qualitative and quantitative approaches from different universities may also provide a greater understanding of technology commercialization and academic entrepreneurship as a whole.